A educação a distância e a formação docente - Moraes, Dinorá de Fátima Gonçalves (2016)
This study was guided by the following question: Is it possible to prepare good teachers for Basic School in Distance Learning (DL) online? The over all objective of this study was to identify and systematize the essential knowledge and skills for the practice of teaching in basic education as well to investigate whe ther the Distance Learning courses which train and prepare future teachers include all the knowledge and skills necessary for teaching practice. This is a qualitative the oretical and bibliographic research that aims to analyze the current stageof the knowledge on this theme. We selected recent papers on this subject, in order to study what has been written by the authors as well to know which are their significant findings. Data were collected from dissertations, thesis and books published on the theme. Preliminarily, the theme of the presentation and contextualization has been made and the argument about the relevance of the study for education. In the second section, we present an overview of the Distance Education in Brazil: coargumentncepts, characteristics, emergence, evolution and regulation. The third section the working environmentin training teachers and students in on line education, targeting to be familiar to Learning Virtual Environments (LVE), analyzing how these new learning spaces are settled and how students and teachers be have in front of the new settings of teaching and learning using Information and Communication Technologies (ICT). In the fourth section aimed to identify which are the essential knowledges and skills that the teacher must master in order to work competently as well to discover which are the personal and professional characteristics of a good teacher in the XXI century. The fifth section studied and analyzed the current situation with in Distance Education is carried out in Brazil. We identified the most significant contributions of Distance Learning to Brazilian Education System in order to contribute to advances in the debate on the effectiveness of teacher training courses in distance education mode online.Finally in the sixth section were made final remarks and presented the study results.